2010
DOI: 10.1021/np900664f
|View full text |Cite
|
Sign up to set email alerts
|

Stylissamides E and F, Cyclic Heptapeptides from the Caribbean Sponge Stylissa caribica

Abstract: In addition to the four known stylissamides, A (1), B (2), C, and D, two new cyclic heptapeptides, stylissamides E (3) and F (4), were isolated from the Caribbean sponge Stylissa caribica. The structures of 3 and 4 were elucidated from a combination of mass spectrometric and NMR spectroscopic data as cyclo-(cis-Pro(1)-Tyr(2)-trans-Pro(3)-Ala(4)-Ile(5)-Gln(6)-Ile(7)) for stylissamide E (3) and cyclo-(trans-Pro(1)-cis-Pro(2)-Phe(3)-Asp(4)-trans-Pro(5)-Arg(6)-Phe(7)) for stylissamide F (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In addition, the analysis of the pharmacological activity data revealed that heptacyclopeptide 7 displayed a higher bioactivity against pathogenic microbes and earthworms than its linear form 6 , which is due to the fact that cyclization of peptides reduces the degree of freedom for each constituent within the ring and thus substantially leads to reduced flexibility, increased potency and selectivity of cyclic peptide. In contrast to synthetic heptacyclopeptide 7 , neither natural stylissamide G [19] nor other heptacyclopeptides of the stylissamide class isolated from the marine sponge Stylissa caribica including stylissamides A-F, H and X [19,27,59,60] are reported to possess pharmacological activity against pathogenic microbes and earthworms. However, literature supports inhibitory activity towards protein translation and cell migration possessed by stylissamide A and X respectively [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analysis of the pharmacological activity data revealed that heptacyclopeptide 7 displayed a higher bioactivity against pathogenic microbes and earthworms than its linear form 6 , which is due to the fact that cyclization of peptides reduces the degree of freedom for each constituent within the ring and thus substantially leads to reduced flexibility, increased potency and selectivity of cyclic peptide. In contrast to synthetic heptacyclopeptide 7 , neither natural stylissamide G [19] nor other heptacyclopeptides of the stylissamide class isolated from the marine sponge Stylissa caribica including stylissamides A-F, H and X [19,27,59,60] are reported to possess pharmacological activity against pathogenic microbes and earthworms. However, literature supports inhibitory activity towards protein translation and cell migration possessed by stylissamide A and X respectively [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Stylissamides A-D are cyclic heptapeptides that were isolated from Stylissa caribica and included three proline residues in stylissamides A, C, & D and four proline residues in stylissamide B [116]. In addition, stylissamides E [117], F [117], G [118], and H [118] were also isolated from S. caribica . Stylissamide E included two proline residues while stylissamide F was a polar peptide with three proline residues [117].…”
Section: Bioactive Peptides From Various Marine Sourcesmentioning
confidence: 99%
“…Arguably the most significant challenge in CP design is our poor understanding of their sequence–structure relationships. The current majority of experimental structural information for small CPs (≤8 amino acids) comes from X‐ray crystal structures and NMR structures in organic solvent . However, X‐ray crystal structures lack dynamic information, providing only a single snapshot among a possible ensemble of structures available in solution.…”
Section: Experimental Design Of Cyclic Peptidesmentioning
confidence: 99%